Evaluating Students' Argumentation Skills Using an Argument-Generating Learning Model Supported Toulmin’s Argumentation Pattern in Physics Concepts - Muslim, Muslim; Sihombing, Rizky Agassy; Zakwandi, Rizki; Karimi, Amir (Universitas Negeri Semarang, 2024)
This study examines the effectiveness of the Argument-Generating (AG) learning model, supported by Toulmin’s Argumentation Pattern, in enhancing students' argumentation skills with a specific focus on the topic of physics. The primary aim is to evaluate how the AG learning model, augmented by Toulmin’s framework, improves students' abilities to construct and defend arguments in the context of physics. Additionally, the research seeks to assess the overall effectiveness of this instructional approach and gather student responses regarding its application. A quasi-experimental method with a pretest-posttest control group design was utilized, involving 50 third-grade Physics Education students at an LPTK in Bandung. These students were divided into an experimental group of 26 students, who engaged with the physics topic using the AG learning model supported by Toulmin’s Argumentation Pattern, and a control group of 24 students, who followed a traditional instructional approach. Quantitative data were collected using an argumentation skills test that assessed students' ability to formulate claims, provide data, construct warrants, and offer backing. The analysis revealed a significant improvement in the argumentation skills of the experimental group, with a very large effect size (d=2.09). This substantial effect indicates that the AG learning model, supported by Toulmin’s Argumentation Pattern, significantly enhances students' argumentation skills. In conclusion, the study demonstrates that the Argument-Generating learning model, when integrated with Toulmin’s Argumentation Pattern, is highly effective in improving students' argumentation skills in physics, underscoring its potential as a valuable instructional strategy.